RETRACTED: An acridone-derived fluorescent off-on probe for detection and in vivo imaging of nitroreductase - Liu, Meicen; Chen, Guanyu; Xu, Lilan; Chen, Tingting; Chen, Wenqian; Chen, Jinghua; Zhang, Xi (Frontiers in Materials, 2023)
Understanding the functions of enzymes in various physiological processes is important, but the design of signaling probes for fast analysis of enzymatic activity is particularly challenging. Herein, a fluorescence-enhanced probe, 10-methyl-2-nitro-acridone (MNA), was synthesized and applied to analyze nitroreductase (NTR) activity in vitro and in vivo. The detection mechanism is based on the nitro group in MNA reacting toward NTR with high reactivity and generating 10-methyl-2-aminoacridone (MAA) accompanied by an obvious fluorescence signal enhancement at 525 nm emission. The probe shows low cytotoxicity, fast response, and high selectivity and sensitivity with a limit of detection as low as 150 ng mL -1 . The probe was also employed for two-photon fluorescence imaging of NTR in zebrafish in vivo revealing the distribution of NTR. Versus existing NTR probes, the proposed probe shows favorable analytical performance including near-infrared light excitation with no other byproducts produced after the reaction. The superior properties of this signaling probe allow it to become a fluorescence imaging candidate in other biosystems.